(untitled) (Global Journal of Human-Social Science, 2017)
In the general economic language any rise in prices is called inflation but it is necessary to make a clear distinction between the causes determining a single non-continuous rise in prices and other circumstances that may cause a continuous and widespread growth of them In the evolution of real economy various events may occur that are able to cause a rise in prices on the whole market These are called inflation shocks In order to analyze these issues more deeply we will suppose that the economy is in a long-term macroeconomic balance and currency exchange rate operates under a flexible regime Also in the initial state the price level is relatively constant and gross domestic product GDP is at its potential level